2022
DOI: 10.1126/sciadv.abm7229
|View full text |Cite
|
Sign up to set email alerts
|

Role of tropical lower stratosphere winds in quasi-biennial oscillation disruptions

Abstract: In 2016, the westerly quasi-biennial oscillation (WQBO) in the equatorial stratosphere was unprecedentedly disrupted by westward forcing near 40 hPa; this was followed by another disruption in 2020. Strong extratropical Rossby waves propagating toward the tropics were considered the main cause of the disruptions, but why the zonal wind is reversed only in the middle of the WQBO remains unclear. Here, we show that strong westerly winds in the equatorial lower stratosphere (70 to 100 hPa) help to disrupt the WQB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The physical mechanisms leading to these enhanced anomalies are yet unclear. We note that the 2015–2017 event corresponds to an anomalous QBO during which the westerly phase in 2015/2016 is extended into mid‐2018, instead of shifting to the easterly phase in 2016/2017 (Figure 4b) (Kang et al., 2022).…”
Section: Resultsmentioning
confidence: 83%
“…The physical mechanisms leading to these enhanced anomalies are yet unclear. We note that the 2015–2017 event corresponds to an anomalous QBO during which the westerly phase in 2015/2016 is extended into mid‐2018, instead of shifting to the easterly phase in 2016/2017 (Figure 4b) (Kang et al., 2022).…”
Section: Resultsmentioning
confidence: 83%
“…Also, we may quantitatively compare the impacts of the extremely positive IOD on the middle latitude quasi‐stationary planetary waves with those of the composite average of the positive IOD events. Additionally, this is the year when the SSW in the SH and the QBO disruption happened for the second time in the record, and there was a strong ZWN1 Rossby wave (Anstey et al., 2021; Kang et al., 2022; Shen et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Coincidentally, 2019 is known for the minor SSW in the SH and the QBO disruption event and is associated with large Rossby wave activities. The cause of SSW includes the anomalous ZWN1 activity in the SH (Shen et al., 2020), whereas the QBO disruption was triggered by the enhanced Rossby waves from the SH (Anstey et al., 2021; Kang et al., 2022). Our results suggest that the Rossby wave forcing may be associated with enhanced ZWN1 activities near 60°S as well as those in ZWN2 near 80°S.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…QBO disruptions do not occur in the historical or future simulations presented here despite its recent occurrences in 2015-2016 (Kang et al, 2020;Osprey et al, 2016) and 2019-2020 (Kang & Chun, 2021) in observations. Kang et al (2022) proposed that the increase in westerly winds in the lower stratosphere near the equator helps weakens the WQBO by facilitating the vertical propagation of westward equatorial waves and suggested that it is possible that QBO disruptions will become more frequent in the future due to changes in background winds. They also found that the QBO disruption-like events occur in 5 out of 10 CMIP6 models in future simulations under the SSP370 scenario despite not being observed in historical simulations.…”
Section: Absence Of the Qbo Disruptionmentioning
confidence: 99%